Catechol‐based co‐deposited carbon fiber surfaces for enhancement of fiber/epoxy composites. Issue 9 (15th June 2020) - Zhang, Mengjie; Liu, Liu; Jin, Lin; Sun, Lihao; Li, Ming; Shang, Lei; Liu, Yu; Ao, Yuhui
Abstract: To improve interfacial adhesion between carbon fiber (CF) and epoxy resin, a low‐cost and environment‐friendly method was developed to treat the CF surface via the bio‐inspired co‐deposition of catechol (Cc) and polyethyleneimine (PEI). It is noteworthy that the deposition process reacts at room temperature with water as solvent, and does not require harsh conditions or the use of toxic reagents. After treatment, the CF/epoxy composites were endowed with excellent mechanical properties and showed increases of 51.9% and 51.7% for flexural strength and ILSS, respectively, in comparison with unsized CF laminates. The analyses of fractured surface morphologies and strengthening mechanism of the composites indicated that the uniformly coated Cc‐PEI on the fiber surface can promote the diffusion and entanglement of the matrix molecular chains and form chemical bonding as well as π‐π stacking, thus effectively improving the interfacial adhesion. In addition, the facile process disclosed in this study can provide a new strategy to not only for CF treating but also expected to be used in the modification of other high performance fiber reinforcement and industrial applications. Abstract :